Local diagnostic reference levels for skeletal surveys in suspected physical child abuse. Issue 2 (May 2021) - Mussmann, B.; Hardy, M.; Rajalingam, R.; Peters, D.; McFadden, S.; Abdi, A.J.
Abstract: Introduction: The purpose was to determine if an age based, local diagnostic reference level for paediatric skeletal surveys could be established using retrospective data. Methods: All children below two years of age referred for a primary skeletal survey as a result of suspected physical abuse during 2017 or 2018 (n = 45) were retrospectively included from a large Danish university hospital. The skeletal survey protocol included a total of 33 images. Dose Area Product (DAP) and acquisition parameters for all images were recorded from the Picture Archival and Communication System (PACS) and effective dose was estimated. The 75th percentile for DAP was considered as the diagnostic reference level (DRL). Results: The 75th percentile for DAP was 314 mGy∗cm 2, 520 mGy∗cm 2 and 779 mGy∗cm 2 for children <1 month, 1–11 months and 12 < 24 months of age respectively. However, only the age group 1–11 months had a sufficient number of children (n = 27) to establish a local DRL. Thus, for the other groups the DAP result must be interpreted with caution. Effective dose was 0.19, 0.26 and 0.18 mSv for children <1, 1–11 months and 12 < 24 months of age respectively. Conclusion: For children between 1 and 11 months of age, a local diagnostic reference level of 520 mGy∗cm 2 was determined. This may be used as an initial benchmark for primary skeletal surveys as a result of suspected physical abuse for comparison and future discussion. Implications for practice: While the data presented reflects the results of a single department, the suggested diagnostic reference level may be used as a benchmark for other departments when auditing skeletal survey radiation dose.